Five Steps to Prevent a Repeat of the 2007–08 Food Crisis - Fan, Shenggen (2010)
Shenggan Fan, Director General of the International Food Policy Research Institute (IFPRI) outlines five strategic measures that will help prevent a rapid surge in agricultural commodity prices. [5 slides]